2014
DOI: 10.1073/pnas.1414189111
|View full text |Cite
|
Sign up to set email alerts
|

Selective oral ROCK2 inhibitor down-regulates IL-21 and IL-17 secretion in human T cells via STAT3-dependent mechanism

Abstract: Rho-associated kinase 2 (ROCK2) regulates the secretion of proinflammatory cytokines and the development of autoimmunity in mice. Data from a phase 1 clinical trial demonstrate that oral administration of KD025, a selective ROCK2 inhibitor, to healthy human subjects down-regulates the ability of T cells to secrete IL-21 and IL-17 by 90% and 60%, respectively, but not IFN-γ in response to T-cell receptor stimulation in vitro. Pharmacological inhibition with KD025 or siRNA-mediated inhibition of ROCK2, but not R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
228
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 201 publications
(243 citation statements)
references
References 41 publications
14
228
0
1
Order By: Relevance
“…At week 12, 42% of patients in the 400 mg once a day cohort and 29% of patients in the 400 mg twice a day cohort achieved a PASI 50 response (Fig. 1B), suggesting a potential clinical benefit of using a lower dosage regimen (200 mg twice a day) of the selective ROCK2 inhibitor KD025, which is 75-to 100-fold more selective for ROCK2 than for ROCK1 (15,21). Interestingly, a recent study demonstrated that inhibition of both ROCK1 and ROCK2 isoforms with pan-ROCK inhibitors potently induces proliferation of primary human keratinocytes in vitro, and might have a negative impact in proinflammatory settings such as psoriasis compared with selective ROCK2 inhibition (22).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…At week 12, 42% of patients in the 400 mg once a day cohort and 29% of patients in the 400 mg twice a day cohort achieved a PASI 50 response (Fig. 1B), suggesting a potential clinical benefit of using a lower dosage regimen (200 mg twice a day) of the selective ROCK2 inhibitor KD025, which is 75-to 100-fold more selective for ROCK2 than for ROCK1 (15,21). Interestingly, a recent study demonstrated that inhibition of both ROCK1 and ROCK2 isoforms with pan-ROCK inhibitors potently induces proliferation of primary human keratinocytes in vitro, and might have a negative impact in proinflammatory settings such as psoriasis compared with selective ROCK2 inhibition (22).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, several groups demonstrated that ROCK2 specifically contributes to regulation of IL-17 secretion in mice and humans (13,15). To explore whether plasma IL-17 levels could be used to monitor response to the KD025 treatment, peripheral blood samples were collected on a monthly basis and cytokine levels were measured by using a Quanterix Simoa platform for biomolecule detection.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations